PENGARUH EKUITAS MEREK DAN PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN ULANG PRODUK MINYAK GORENG PADA MASA PANDEMI COVID-19 - Khotim Fadhli; Elsa Dwi Aprilia; Ino Angga Putra (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2021)
This study aims to determine the effect of brand equity and consumer behavior on repeat purchases. This type of research uses quantitative research. The data collected in this study used questionnaires or submitted written questions to collect data from respondents with a total of 79 respondents. Respondents were taken from the customers of the Mitra Swalayan Jombang store. The data were processed using multiple linear regression analysis using the SPSS version 26 computer program. This study showed positive and significant results from the influence of brand equity variables (X1) and consumer behavior (X2) on the repurchase variable (Y). Brand equity against repurchase is a component that must exist. Because brand equity will make the product attractive to consumers and people are looking for to consume again. Consumer behavior towards repurchase is something that must be known by a marketer in order to understand how consumers make decisions or choose the goods to be purchased. Based on the results of this study, several conclusions can be drawn, that brand equity and consumer behavior variables affect repeat purchases at Mitra Swalayan Jombang.